2015
DOI: 10.1007/s10654-014-9986-0
|View full text |Cite
|
Sign up to set email alerts
|

Preterm and postterm birth in immigrant- and Swedish-born parents: a population register-based study

Abstract: Ethnic minorities/immigrant groups tend to have increased risk for preterm birth. Less is known about this risk in diverse immigrant groups, couples of mixed ethnic-origin and in relation to duration of residence. Data from the Swedish Medical Birth Register on 1,028,303 mothers who gave birth to 1,766,026 singleton live born infants (1982-2002), was linked to the Education and Total Population Registers. Immigrant parents were identified by country of birth. Risk of early preterm, late preterm and postterm bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
6
21
2
1
Order By: Relevance
“… 25 Another study showed that Swedish fathers and non-Swedish mothers had higher risks of preterm birth but lower risks of post-term birth. 18 In a Canadian study, Canadian-origin fathers and foreign born mothers had lower birth weight and the birth weight was lower when they lived in the same ethnic high concentration area. 26 …”
Section: Discussionmentioning
confidence: 98%
“… 25 Another study showed that Swedish fathers and non-Swedish mothers had higher risks of preterm birth but lower risks of post-term birth. 18 In a Canadian study, Canadian-origin fathers and foreign born mothers had lower birth weight and the birth weight was lower when they lived in the same ethnic high concentration area. 26 …”
Section: Discussionmentioning
confidence: 98%
“…Confounders were chosen a priori based on literature. [33][34][35][36][37][38][39] We adjusted for the mother's country of birth, educational level, smoking status, parity (except in the sensitivity analyses of parity), age, calendar year of birth and BMI. Further, all models were analysed with and without adjustment for BMI when estimating effects of PsA on different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies found higher risks, some found similar risks and others found mixed risks for specific Indian, Pakistani and Bangladeshi groups . There have been relatively few studies from other high‐income countries . Although a number of socio‐economic, obstetric and genetic explanations have been proposed to explain these differences, the mechanisms or reasons behind them are not well understood.…”
Section: Introductionmentioning
confidence: 99%